The Influence of Self-Regulated Learning and Social Support on Academic Resilience in Full-Time Students Compared to Working Students: An Explanatory Survey - Martina, Feny; Friantary, Heny; Rakhmanina, Lisa (UNIB Press, 2025)
Today's complex academic demands require full-time and working students to use self-regulated learning skills, social support, and academic resilience to manage learning pressures. This study aims to investigate the influence of self-regulated learning and social support on academic resilience among full-time and working English students in Bengkulu. Specifically, it compares academic resilience between these two groups, providing insights into how these characteristics interact with different student commitments. Using an explanatory survey design, this study investigated the causal relationships between self-regulated learning (X1), social support (X2), and academic resilience (Y) among English students who were full-time and working in Bengkulu. Questionnaires were used to collect the data. The samples were selected randomly consisting of 100 respondents—65 full-time and 35 working students. The data were analysed using multiple regression analysis to identify significant and dominant factors (whether X1 or X2) influencing Y. The research findings found proof that both factors significantly influenced academic resilience, but with different dominant patterns in each student group. Independent learning was the most dominant factor for full-time students (R² = 0.788), since it reflected its strong role in an academic environment. Conversely, social support was the dominant factor for working students (R² = 0.756), indicating the important role of support from the social environment in helping students cope with time and energy constraints. These findings revealed the significance of adjusting pedagogical strategies to students' levels and needs in English language learning in higher education, thereby building their academic resilience.